THE INTERNET, CIVIC ENGAGEMENT, AND NEW CIVIL SOCIETY IN INDONESIA: A LESSON FROM TWO TALES - Muhtada, Dani (Tadulako Law Review, 2018)
This article discusses two legal cases happened in 2009: the cases of Prita Mulyasari and Bibit-Chandra. These cases are interesting as they involved the use of Internet as a medium for an effective civic engagement in controlling law enforcement. The response of the Indonesian public to the cases of Prita and Bibit-Chandra and their success stories in controlling the authorities indicate a significant existence of the so-called an â€œonline parliamentâ€, which signed an emergence of a new civil society movement in the modern Indonesia. This online parliament is much more inexpensive and independent than the conventional parliament. However, it might only work for political issues that attract much public attention and might be only accessible for those who have the access to the Internet.